Trade, inequality, and subjective well-being: Getting at the roots of the backlash against globalization - Barbara Dluhosch (Luxembourg Income Study (LIS), 2018)
Many countries in the Western hemisphere are currently experiencing a backlash against globalization. Most of the research examining the issue has concentrated on international specialization and within-country income inequality as main drivers of the backlash. Doing so, the discussion has primarily revolved around the question whether and to what extend the income distribution has widened and whether trade is responsible indeed. However, political trends may be more grounded in perceptions than facts, thus giving rise to inappropriate populist policies. The difference matters all the more as the former may be accentuated by (social) media. Drawing mainly on subjective well-being (SWB) data from theWorld Values Survey (WVS) and income statistics from the Luxembourg Income Study (LIS), this paper shows in an international cross-section analysis that income inequality is perceived very differently depending on openness to trade. The relevance of perceptions has wider politico-economic implications in that it carries the risk of costly anti-trade policies, without necessarily narrowing the income distribution.
Keywords: F61; F13; D63; D31; 330; Subjective Well-Being; International Trade; Income Distribution; Inequality; Identity